One-loop string amplitudes in AdS5 ×S5: Mellin space and sphere splitting - Aprile, F. [UNESP]; Drummond, J. M.; Glew, R.; Santagata, M. (Springer Nature, 2023)
We study string corrections to one-loop amplitudes of single-particle operators Op in AdS5×S5. The tree-level correlators in supergravity enjoy an accidental 10d conformal symmetry. Consequently, one observes a partial degeneracy in the spectrum of anomalous dimensions of double-trace operators and at the same time equality of many different correlators for different external charges pi=1,2,3,4. The one-loop contribution is expected to lift such bonus properties, and its precise form can be predicted from tree-level data and consistency with the operator product expansion. Here we present a closed-form Mellin space formula for 〈 Op1Op2Op3Op4〉 at order (α′)3, valid for arbitrary external charges pi. Our formula makes explicit the lifting of the bonus degeneracy among different correlators through a feature we refer to as ‘sphere splitting’. While tree-level Mellin amplitudes come with a single crossing symmetric kernel, which defines the pole structure of the AdS5× S5 amplitude, our one-loop amplitude naturally splits the S5 part into two separate contributions. The amplitude also exhibits a remarkable consistency with the corresponding flat space IIB amplitude through the large p limit.
Keywords: 1/N Expansion; AdS-CFT Correspondence; Scattering Amplitudes